Effect of the Microcrack Inclination Angle on Crack Propagation Behavior of TiAl Alloy - Feng, R.C.; Lu, J.T.; Li, H.Y.; Cao, H.; Rui, Z.Y. (Проблемы прочности, 2017)
Molecular dynamics simulation was employed to make the model of crack propagation for singlecrystal y-TiAl alloy. The effects of the angle between a microcrack and loading direction on crack propagation were studied through the analysis of the atomic configurations and stress—strain curves in the paper. The results show that the time for the emission of first dislocation and the yield stress value decrease with the angle. The crack propagation occurs by the submain crack mechanism, which becomes more obvious as the angle increases and the number of stacking faults and stair-rod dislocations decreases.